Examine the influence of competencies, placements, and workloads on employee performance - Pratama, Bayu Indra; Sutianingsih, Sutianingsih (Journal of Management and Digital Business, 2025)
This study aims to empirically examine the effects of work competencies, job placement, and workload on employee performance at PT BPR Bank Djoko Tingkir in Sragen Regency. The study adopts a quantitative approach using a census (saturated sampling) method, in which all 115 employees in the population were included as respondents. Data were collected through a questionnaire and analyzed using multiple linear regression. Before hypothesis testing, a series of data quality and assumption tests were conducted, including validity, reliability, and normality tests, as well as tests for multicollinearity and heteroscedasticity. Partial effects were evaluated using t-tests, while the simultaneous effect of the independent variables was assessed using an F-test. The results show that work competencies have a positive and significant effect on employee performance. Job placement is also found to have a positive and significant effect on employee performance. In addition, workload has a positive and significant effect on employee performance. Simultaneously, work competencies, job placement, and workload significantly influence employee performance. These findings underscore the importance of strengthening competencies, ensuring appropriate placement, and managing workload to support optimal employee performance.